The Relationship Of The Level Of Elderly Knowledge About Dementia And The Risk Of Dementia - Zhahira, Anisya Virotika; Maryam, Raden Siti; Riyanti, Eska; Resnayati, Yeti; Nurhasanah, Aan; Pudjiati, Pudjiati (PT. Nursing Genius Care, 2024)
Background:The growing elderly population will bring many changes that impact health problems, such as dementia which affects cognitive function. Objective: Analyzing the relationship between the level of knowledge of the elderly about dementia and the risk of developing dementia at the Mekarsari Village Health Center. Methods:This study uses a quantitative approach that is descriptive analytic, using a cross sectional design. The sample in this study were 85 elderly who were taken using purposive sampling. Data analysis used the chi square test. The instrument used to measure the possibility of dementia in respondents is a modified standard instrument of the HVLT (Hopkins Verbal Learning Test Version) and modified DKAS (Dementia Knowledge Assessment Scale). Results:The results showed that there was a relationship between the level of knowledge of the elderly about dementia and the risk of dementia with a total p value of 0.030 (<0.05). Conclusion:The level of knowledge about dementia in elderly respondents is mostly knowledgeable. The majority of the risk of dementia in the elderly is in the normal category.